Profit Margin Assessment of Sheep Marketing: A Panacea for Sustainable Small-scale Livestock Enterprise in Gombe State, Nigeria - Abdullahi Saleh; Ya'u Adamu; Haruna Abubakar Alkali; Kubra Hamidu; Ya'u Shuaib (Universitas Negeri Malang, 2018)
This paper assessed the profitability of small-scale sheep marketing in Gombe Metropolis. Four sheep markets were purposively selected for their popularity in small ruminants marketing. A multi-stage sampling technique was used to select 91 sheep marketers these markets. Data were collected using structured questionnaire and were analysed using descriptive statistics, farm budget and maximisation of consumer satisfaction models. The result revealed that purchasing cost for ram and ewe constituted 92.59% and 91.50% of the total marketing costs respectively. The result further revealed the average net income of ₦4,922.46 (13.72) per head of animal was realised. The gross and operating ratios for the respective animals were < 1; meaning that the business was profitable. Also, the returns per naira invested for ram and ewe were ₦0.17 (0.00048) and ₦0.18 (0.0005) respectively. The marketing coefficient (134.80%) of Tike-babba market, revealed to be most efficient. Inadequate capital was critical; this was attributed to insufficient sources of credits. However, improvement in the existing infrastructural facilities will help promote expansion of the present scale of the enterprise operations. Governments and other financial institutions should also do more to extend funds in the form of soft loans to the marketers, so as to improve efficiency.Keywords: Market; Profitability; Efficiency; Sheep; Small-scale; GombeJEL Classification: L10, Q13